A Study on Preclinical Safety and Efficacy of MCP I Conjugated Gold Nanoparticles based oral contraceptive using Biomarkers of Reproductive Tissues and Blood Serum of Male Albino Wistar Rats (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
Characterized MCP I fraction of Carica papaya seeds is being considered a potential contraceptive agent. Utilization of gold nanoparticles as a carrier molecule enhanced its targeted bioavailability, biocompatibility, in vitro stability against blood serum and pH gradient. In this study, preclinical safety and efficacy were assessed employing concerned biomarkers of blood serum and excised reproductive tissues for further approval of this nanoformulation. Experimental groups A, B & C were consists of vehicle control, orally treated with MCP I (50 mg/kg body wt./day) and MCP I conjugated gold nanoparticle (200µg/kg body wt./day) containing nine male albino Wistar rats in each. Three animals were sacrificed monthly interval during 90 days of investigation period. No significant differences were examined in markers of blood serum i.e., cholesterol, creatinine, lactate dehydrogenase, creatine kinase, bilrubin, urea, triglyceride, HDL and concentrations of testosterone, luteinizing hormone and follicle stimulating hormone except drastic reduction in SGOT (p< 0.001) and SGPT (p< 0.05; p< 0.01; p< 0.001) in group C. The glycogen, cholesterol and lactate dehydrogenase level in testicular tissues, sialic acid and fructose corresponded to epididymal and seminal vesicles, respectively, demonstrated insignificant changes. Significant diminution was recorded in the level of L-carnitine and α-glucosidase at 60 days in group B (p< 0.05) and 30 days in group C (p< 0.01; p< 0.001) of epididymal tissues. Prostatic acid phosphatase was increased (p< 0.05; p< 0.01) in group C. While antioxidant biomarkers in testicular tissues viz., lipid peroxidase, superoxide dismutase, reduced glutathione and catalase were revealed insignificant alteration. Thus, status of biomarkers indicate that synergistic effect of MCP I conjugated gold nanoparticle was found to be targeted, safe and effective for oral contraception in male albino rats at highly reduced dosage compared to pure MCP I treated animals which may open new avenues for clinical development.